Engaging with the pragmatics of relational thinking, leverage points and transformations – Reply to West et al. Issue 1 (1st January 2021) - Raymond, Christopher M.; Kaaronen, Roope; Giusti, Matteo; Linder, Noah; Barthel, Stephan
ABSTRACT: We reply to 'A relational turn for sustainability science?' by West et al. We commend West et al. for their salient comments about the relational turn. Yet the article leaves us wondering about the methodological challenges and pragmatics of relational thinking. The authors omitted important tensions in relational thinking discussion about how to assess dynamic socio-ecological systems, and how to lever change for sustainability. Whilst relational thinking is helpful, researchers inevitably need to make strategic choices about where to divide system components if the goal is to systematically assess relations and to promote transformations toward sustainability. Where and how to 'apply the knife' inevitably is informed by one's ontological starting point (view of reality) and personal epistemological beliefs. We outline three questions to be answered in order to more firmly establish relational thinking in sustainability science: If systems and processes are continually unfolding, how do we identify where to lever change for sustainability? In relational thinking, can we explain human action outside of the shared 'activity of experiencing'? If society and ecology is co-constituted, how can relational approaches be used to understand unfolding and cascading effects in complex systems? We conclude with future directions for a solutions-oriented sustainability science agenda.